Preventing stunting with complementary feeding (MP-ASI) using local food ingredients - Riyanti, Eka; Nurlaila, Nurlaila; Susilowati, Yuli; Bilqis, Zalfa Almaida Layana; Anisah, Nurul; Prayoga, Enggal Agus; Asiyah, Siti; Humairoh, Rida (Universitas Muhammadiyah Magelang, 2025)
Stunting leaves children susceptible to illness and impairs brain development, ultimately hindering the creation of a strong, capable generation. The purpose of this program was to equip healthcare cadres and community members with the knowledge to prepare healthy and affordable complementary feeding (MP-ASI) using locally available ingredients to improve children's nutritional status. With three cases of stunted toddlers identified in Jatimulya Village, there was an urgent need for intervention. The training utilized local food ingredients, such as moringa leaves, spinach, and catfish. The methods employed included lectures, simulations, and a cooking competition. The evaluation showed a significant increase in the knowledge of both cadres and mothers of toddlers, with average scores rising from 81.6 to 92.3 after the educational intervention. A competition was also held, where representatives from each sub-village (RW) prepared nutritionally dense main and snack dishes, with three winning entries selected. In conclusion, utilizing local food-based complementary feeding can be an effective strategy for stunting prevention in Jatimulyo Village.